Case Report: A case of Crohn's disease with right atrial thrombosis - Hu, Zehang; Gao, Yi; Fan, Shumin (Frontiers in Pediatrics, 2024)
Crohn's disease (CD) is a chronic, non-specific inflammatory disease of the intestinal tract with an unknown etiology.It presents with clinical symptoms such as abdominal distension, abdominal pain, diarrhea, bloody stools containing mucus or pus, and other manifestations. CD has a prolonged and chronic course and can lead to various complications that significantly impact patients' quality of life. Patients with CD have hypercoagulable blood and are prone to thromboembolic diseases, which pose a serious threat to their lives. Several studies have indicated that inflammatory bowel disease is a risk factor for venous thromboembolism. The pathogenesis involves abnormalities in the coagulationanticoagulation system, fibrinolytic system, platelets, vascular endothelial dysfunction, as well as the effects of therapeutic agents. In this case report, we present a rare case of a 15-year-old female patient with active Crohn's disease complicated by the presence of a right atrial thrombus. Laboratory tests revealed abnormalities in both the coagulation-anticoagulation system and fibrinolysis system in the patient. The initial diagnosis, based on transthoracic echocardiography and contrastenhanced echocardiography, confirmed the presence of a thrombus in the right atrium. Subsequent administration of anticoagulant and thrombolytic therapy resulted in gradual reduction in size until complete disappearance, as evidenced by dynamic monitoring. Ultrasound examination is considered as the preferred method for follow-up evaluation in patients with Crohn's disease due to its ability not only to assess gastrointestinal complications but also to aid early identification of cardiovascular complications, thereby enabling timely intervention and treatment -which remains our primary focus of research and effort.